Artificial Intelligence based Point of Care Device in Advanced Medical Diagnostic Techniques - Suraj Kumar; Neeraj Kumar Pandey; Manita Paneri; Rajender Kumar (International Journal of Biomedical Innovations and Engineering, 2025)
Application of Point-of-Care Testing (POCT) at medical sites provides instant diagnostic results that help doctors make quick decisions for patient care. The traditional point-of-care testing equipment faces restrictions because they test single parameters and experience calibration problems in addition to inefficient data management systems. POCT technology benefits from the integration of Artificial Intelligence (AI) which creates a novel system to solve current operational limitations. The presented study introduces an intelligent POCT device enabled by AI for multiparameter examination with automated calibration and sophisticated data handling functions. Biochemical diagnosis through simultaneous biomarker detection becomes more precise and efficient when using the multiparameter analysis feature. The device's automatic calibration function guarantees repetitive and accurate measurements which requires less human intervention and fondly minimizes human errors during operation. AI-enabled data management features of the system enable users to store data in the cloud while automating its analysis to improve healthcare setting data accessibility and interoperability functionality. An AI-based point-of-care testing system will boost clinical diagnostic precision which leads to better patient results while enabling immediate medical decision-making for medical staff. This ground breaking approach uses advanced methods to reduce errors and optimize calibration and data handling therefore creating new benchmarks for AI-hearted point-of-care diagnostic technologies.
Keywords: AI-Powered POCT; Auto-Calibration Technology; Healthcare Data Integration; Multipara meter Testing; Real-Time Diagnostics